PRODUCTIVE WAQF MANAGEMENT ASSISTANCE FOR UMMAH WELFARE: PENDAMPINGAN PENGELOLAAN WAKAF PRODUKTIF UNTUK KESEJAHTERAAN UMMAT - Churahman, Taufik; Haryanto, Budi; Nisak Aulina, Choirun; Gita Safitri, Silvia (Antis-publisher, 2024)
As is the case in other regions, the management of waqf land in the Penataran Sewu Branch, Sidoarjo is not yet optimal, even though it has great potential if managed properly. This is caused by the knowledge, insight and skills of the Sweu Penataran Branch in managing waqf land to become productive rice field rentals and making waqf land as a medium of da'wah which is still limited. Therefore, a community service program was carried out with the aim of the Muhammadiyah leadership and members launching the Sewu Upgrading. To achieve the goal, several methods of activity were used including coordination, counselling, training, as well as mentoring and monitoring evaluation. The results of the community service program show that the community service program has been carried out well, with organized land waste management and the provision of independent treatment by members who grumble at Muhammadiyah who are productive. Muhammadiyah leaders and members gain knowledge, insight and skills in managing waqf land into productive land so that it can become a media for da'wah bil hal and become an example for the community and other branches in managing waqf land